Antioxidant, antibacterial, antitumor, antifungal, antiviral, anti-inflammatory, and nevro-protective activity of Ganoderma lucidum: An overview - Cör Andrejč, Darija; Knez, Željko; Knez Marevci, Maša (Frontiers in Pharmacology, 2022)
Ganoderma lucidum is a very popular medicinal mushroom that has been used in traditional Chinese medicine for many years. In an ancient medicine is also known as the mushroom of immortality. It has a wide range of pharmacological and therapeutic properties and has been used for many years as a health promoter. It contains various biologically active compounds that improve the immune system and have antioxidant, antitumour, antimicrobial, anti-inflammatory and antifungal properties. Active compounds include triterpenoids and polysaccharides, as well as proteins, lipids, phenolics, sterols, etc. In the following review, we briefly summarize biological activities like are antioxidant, anti-bacterial, anti-fungal, antitumor, anti-viral, anti-inflammatory activity.